2015
DOI: 10.12938/bmfh.2015-005
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lactosucrose suppresses influenza A (H1N1) virus infection in mice

Abstract: This study examined the effects of lactosucrose (4G-β-D-galactosylsucrose) on influenza A virus infections in mice. First, the effects of lactosucrose on fermentation in the cecum and on immune function were investigated. In female BALB/c mice, lactosucrose supplementation for 6 weeks promoted cecal fermentation and increased both secretory IgA (SIgA) levels in feces and total IgA and IgG2a concentrations in serum. Both the percentage of CD4+ T cells in Peyer’s patches and the cytotoxic activity of splenic nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Metabolites are released from the gut microbiota, especially SCFAs such as acetate and butyrate, in addition to the anti-inflammatory cytokines linked to reduced pulmonary pathology in both bacterial (Bernard et al 2015;Vieira et al 2016) and viral infections (Kishino et al 2015). Galvão et al have shown that the absence of GPR43, a receptor for acetate, leads to increased susceptibility to Klebsiella pneumoniae infection, with uncontrolled proliferation of bacteria and to increased inflammatory response.…”
Section: The Microbiota Gut-lung Axis and Immune Response In Obesitymentioning
confidence: 99%
“…Metabolites are released from the gut microbiota, especially SCFAs such as acetate and butyrate, in addition to the anti-inflammatory cytokines linked to reduced pulmonary pathology in both bacterial (Bernard et al 2015;Vieira et al 2016) and viral infections (Kishino et al 2015). Galvão et al have shown that the absence of GPR43, a receptor for acetate, leads to increased susceptibility to Klebsiella pneumoniae infection, with uncontrolled proliferation of bacteria and to increased inflammatory response.…”
Section: The Microbiota Gut-lung Axis and Immune Response In Obesitymentioning
confidence: 99%
“…TLR stimulation by cell wall components and flagellin of gut microbiota is necessary for mounting the immune responses towards influenza. In contrast, oral SCFA-induced anti-inflammatory actions are attributed to decreased pulmonary pathology following bacterial and viral infections in mice ( 36 ). Effectively engaging PRRs expressing innate cells with gut- or non-microbial ligands is essential for the protective mechanism, independent of adaptive immunity during exposure to a pathogen or secondary infection.…”
Section: Microbiota and Immunitymentioning
confidence: 99%
“…SCFAs are produced by many enteric bacterial species and act through free fatty acid (FFA) receptors or epigenetic regulation of immune cells to promote broad anti-inflammatory effects (56). SCFA administration is linked to reduced pulmonary pathology following both and viral and bacterial infection in mice (57)(58)(59). Overall, these studies suggest that recognition of the gut microbiota, as well as specific bacterial metabolites, primes the immune response to counter microbial challenges in the lung.…”
Section: Immunity In the Lungsmentioning
confidence: 99%